Analysis of speed using optocoupler sensors on electric boats in Sayung Demak - Aisa Fitriani Dwi Maharani; Supari; Satria Pinandita (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2024)
In the Indonesian archipelago, boats play a major role in people's daily mobility. In the realm of transportation, especially on sea vessels, it is crucial to keep an eye on the circumstances and state of affairs when traveling long distances. The objective of this study is to use an optocoupler sensor based on the Internet of Things (IoT) and a real-time monitoring technique to track the speed of an electric boat. This instrument can be tested using three different treatments: low-level gas, medium-level gas, and high-level gas with five repetitions. Motor speed was measured at 938 Rpm with a Knot difference of 0.7 utilizing XSpeed and an optocoupler sensor for low-speed measurements. Using an optocoupler sensor and XSpeed, the medium speed tests yielded a motor speed of 1205.6 Rpm and a Knot difference of 1.7. Using an optocoupler sensor and XSpeed, high-speed measurements yielded a motor speed of 1985.4 Rpm and a Knot difference of 1.2. Because the Blynk application may display data of both boat speed and motor rotational speed, readings obtained from the optocoupler sensor yield higher accuracy than those obtained from the comparison application XSpeed